Integrin‐linked kinase regulates the rate of platelet activation and is essential for the formation of stable thrombi - Jones, C; Tucker, K; Sasikumar, P; Sage, T; Kaiser, W; Moore, C; Emerson, M; Gibbins, J (Wiley, 2014)
Background: Integrin‐linked kinase (ILK) and its associated complex of proteins are involved in many cellular activation processes, including cell adhesion and integrin signaling. We have previously demonstrated that mice with induced platelet ILK deficiency show reduced platelet activation and aggregation, but only a minor bleeding defect. Here, we explore this apparent disparity between the cellular and hemostatic phenotypes. Methods: The impact of ILK inhibition on integrin αIIbβ3 activation and degranulation was assessed with the ILK‐specific inhibitor QLT0267, and a conditional ILK‐deficient mouse model was used to assess the impact of ILK deficiency on in vivo platelet aggregation and thrombus formation. Results: Inhibition of ILK reduced the rate of both fibrinogen binding and α‐granule secretion, but was accompanied by only a moderate reduction in the maximum extent of platelet activation or aggregation in vitro. The reduction in the rate of fibrinogen binding occurred prior to degranulation or translocation of αIIbβ3 to the platelet surface. The change in the rate of platelet activation in the absence of functional ILK led to a reduction in platelet aggregation in vivo, but did not change the size of thrombi formed following laser injury of the cremaster arteriole wall in ILK‐deficient mice. It did, however, result in a marked decrease in the stability of thrombi formed in ILK‐deficient mice. Conclusion: Taken together, the findings of this study indicate that, although ILK is not essential for platelet activation, it plays a critical role in facilitating rapid platelet activation, which is essential for stable thrombus formation.